2020
DOI: 10.1002/rcs.2107
|View full text |Cite
|
Sign up to set email alerts
|

Association of demographic, clinical, and hospital‐related factors with use of robotic hysterectomy for benign indications: A national database study

Abstract: BackgroundWe examined the association of patient factors, gynecologic diagnoses, and hospital characteristics with utilization of the robotic approach for benign hysterectomy.MethodsWe performed cross‐sectional study of women (n = 725 050) undergoing hysterectomies in the 2012 to 2014 National Inpatient Sample.ResultsA total of 725 050 women underwent inpatient hysterectomy for benign indications: 70345 (10%) were performed robotically. Women were more likely to receive robotic hysterectomy at teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In our study, African American women underwent most myomectomies but had the lowest proportion of MIM. A large body of research has shown racial disparities in women undergoing hysterectomy 6 , 12 , 14 with an independent increase in surgical complications in African American and Asian American women; one study showing an elevated odds of almost every category of medical/surgical complications in African American women as well as risk of readmission. 21 – 23 A 2020 study by Pollack et al showed that African American, Hispanic, and Asian/Pacific Islander women eligible for minimally invasive hysterectomy were more likely than Caucasian women to undergo an open hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, African American women underwent most myomectomies but had the lowest proportion of MIM. A large body of research has shown racial disparities in women undergoing hysterectomy 6 , 12 , 14 with an independent increase in surgical complications in African American and Asian American women; one study showing an elevated odds of almost every category of medical/surgical complications in African American women as well as risk of readmission. 21 – 23 A 2020 study by Pollack et al showed that African American, Hispanic, and Asian/Pacific Islander women eligible for minimally invasive hysterectomy were more likely than Caucasian women to undergo an open hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Gynecological patients with benign (i.e., fibroids) or malignant disease or comorbidities (i.e., obesity) no longer have to be subjected to open laparotomy, but instead benefit from both surgical and post-surgical advantages offered by robotic minimally invasive surgery. 6,7,10 Once laparoscopic assisted hysterectomy techniques began being used, patient recovery and satisfaction were remarkably improved compared to prior patients receiving either the AH or VH procedures. Not long afterwards, most of our clinic hysterectomy patients received the 2006 McCarus Technique of TLH which required both 5 mm and 10 mm trocars and the use of an ultrasonic energy device.…”
Section: Discussionmentioning
confidence: 99%
“…There have been barriers to robotic surgical platforms in the past; namely the expense of the platform for hospitals and patient billing, training of users, and justification of use via clinical evidence of benefit. 4,7,9 The robotic systems have been in larger institutions for 20 years and in gynecological use for 15. 4 Short and long term clinical benefit data for surgeons and patients have been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations